2019
DOI: 10.1177/1043454219836961
|View full text |Cite
|
Sign up to set email alerts
|

Composing Sexuality in the Midst of Adolescent Cancer

Abstract: I said nothing for a time, just ran my fingertips along the edge of the human-shaped emptiness that had been left inside me.-Murakami (2007, p. 132).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…For example, children and youth often experienced social isolation and difficulties with social reintegration 23–27 . Other studies highlighted disruptions to one's sexual identity due to cancer 25,28–30 . Some findings suggested that sexuality was subverted at the expense of cancer survivorship, 28 essentially “freezing” a child's development at the time of their cancer diagnosis, 25 which resulted in reduced sexual drive and sexual activity 25,28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children and youth often experienced social isolation and difficulties with social reintegration 23–27 . Other studies highlighted disruptions to one's sexual identity due to cancer 25,28–30 . Some findings suggested that sexuality was subverted at the expense of cancer survivorship, 28 essentially “freezing” a child's development at the time of their cancer diagnosis, 25 which resulted in reduced sexual drive and sexual activity 25,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies highlighted disruptions to one's sexual identity due to cancer 25,28–30 . Some findings suggested that sexuality was subverted at the expense of cancer survivorship, 28 essentially “freezing” a child's development at the time of their cancer diagnosis, 25 which resulted in reduced sexual drive and sexual activity 25,28 . Soanes and Gibson found that a “fragility of self” arose due to cancer‐induced hair loss 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, given the seriousness of cancer and its treatment, sexuality often tends to take a backseat to survival in conversations and focus with patients. Having relationships and developing a sense of belonging, however, are deep human needs, and sexuality is an important component of these needs [43]. Establishing a sexual identity is an essential part of the AYA experience, and if these issues are not addressed among the cancer survivor community, there is a risk for poor outcomes such as relationship and sexual problems later in life [44,45].…”
Section: Body Image Sexuality and Relationshipsmentioning
confidence: 99%
“…That said, although some survivors may delay some aspects of their psychosexual experiences, not all are distressed by this and so providers should understand survivors' perceptions rather than comparing to normative milestones alone [38]. Overall, there needs to be more space for survivorship stories to include sex, sexuality, and intimacy in clinical encounters with AYA; patient education materials; online/social media; support groups; and literature [43].…”
Section: Body Image Sexuality and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation